Ecotourism impact assessment on environment in protected areas of Serbia: A case study of Gornje Podunavlje Special Nature Reserve - Stojanović, Vladimir; Mijatov, Maja; Dunjić, Jelena; Lazić, Lazar; Dragin, Aleksandra; Milić, Dubravka; Obradović, Sanja (Geographica Pannonica, 2021)
Ecotourism is a nature-based type of tourism, especially represented within protected areas. No matter the fact, just like the other selective types of this sector, ecotourism might affect the environment. In a process of writing the Visitor Management Plan in the Gornje Podunavlje Special Nature Reserve (SNR) in 2019, one part of the study was related to general projection of the ecotourism development impact on eco-educational paths within this SNR. The research was conducted throughout November 2019, in the form of interviews. The sample obtained 12 experts for nature protection, who stated their attitudes on three important topics: tourism in protected areas in general, tourism in the Gornje Podunavlje SNR and ecotourism within three concrete sites: Karapandža, Štrbac and Bestrement.
Keywords: ecotourism; protected areas; impact assessment; experts’ attitudes; nature protection; plant sensitivity; animal sensitivity